Amino silanized nano-cellulose for deacidifying and reinforcing paper and preparation method of amino silanized nano-cellulose
By modifying pulp fibers with aminosilane coupling agent and preparing aminosilanized nanocellulose, the problems of mechanical strength and shortening of service life of acid paper due to acidic hydrolysis are solved, effectively deacidification and reinforcement of acidic paper are achieved, and the mechanical properties and service life of the paper are improved.
Patent Information
- Application Number
- CN202411862254.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to effectively solve the problems of mechanical strength and shortened service life caused by acidic paper due to acidic hydrolysis.
The pulp fibers were modified by aminosilane coupling agent, and aminosilanized nanocellulose was prepared by mechanical treatment as a deacidifier and reinforcement for paper.
Effective deacidification and reinforcement of acidic paper is achieved, the bonding force between fibers and the mechanical properties of the paper are improved, and the service life of the paper is extended.
Smart Images

Figure CN119877309A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass chemical industry, and specifically relates to aminosilanized nanocellulose for deacidification and reinforcement of paper and a preparation method thereof. Background Art
[0002] The aging of paper mainly involves the acid hydrolysis process of paper fibers. During this process, the degree of polymerization of cellulose decreases, resulting in a weakening of the mechanical strength of the paper. This phenomenon is particularly evident in modern and contemporary ancient books made using acidic papermaking technology and paper artifacts collected in museums. Specifically, acid hydrolysis is caused by hydrogen ions attacking the glycosidic bonds in the fibers, which causes the connection between glucose units to break, forming new hydroxyl groups, and thus shortening the cellulose chains and reducing the degree of polymerization. Since the physical strength of paper is closely related to the degree of polymerization and length of its fibers, as the acid hydrolysis intensifies, the mechanical properties of the paper will gradually deteriorate. In view of this, it is particularly important to deacidify and strengthen these acidic papers.
[0003] During the acid hydrolysis process, paper fibers will not only break, but also produce protons, causing the pH value of the paper to gradually decrease, thereby accelerating the acid hydrolysis reaction. The paper deacidification process mainly involves adding alkaline substances to the paper to neutralize the acidic components therein, and leaving a certain alkaline reserve inside the paper to neutralize the newly generated acid in the future, thereby inhibiting acid hydrolysis and extending the service life of the paper. At present, large-scale paper deacidification technology is mainly divided into two categories: gas phase deacidification and liquid phase deacidification. Gas phase deacidification is to vaporize the alkaline substance and make it penetrate into the paper, but the effect of this method is relatively limited. In contrast, liquid phase deacidification uses solvents to evenly penetrate the alkaline substance into the paper, which is a more thorough process. There are many commonly used liquid phase deacidification materials, such as the use of magnesium (II) nanoparticles in non-polar or polar environments for acidic paper deacidification (M. Jablonsky, J. Sima, The role of magnesium species in paper deacidification. A review, Journal of Cultural Heritage 61 (2023) 194-200). There are also reports on the use of nanolime dispersed in organic solvents for paper deacidification (S. Bastone, DFCMartino, V. Renda, ML Saladino, G. Poggi, E. Caponetti, Alcoholic nanolimedispersion obtained by the insolubilisation-precipitation method and itsapplication for the deacidification of ancient paper, Colloids and Surfaces-Physicochemical and Engineering Aspects 513 (2017) 241-249.). The patent of Fan Yining et al. (CN117107548A) uses PPFOEMA to form a coating layer on the surface of calcium hydroxide and magnesium hydroxide, so that they are dispersed in a fluorocarbon medium for liquid phase deacidification and enhancement of paper. In addition, the patent of Zhang Xiwen et al. (CN113186754A) uses metal salts for paper deacidification research.
[0004] For aged paper, reinforcement treatment is required to extend its service life. Existing reinforcement methods mainly include natural material reinforcement (He Bei, Xu Guibin, Fan Huiming, et al. Research progress on deacidification and enhancement of ancient books [J]. China Papermaking, 2019, 38(08): 73-81.), in-situ reactive reinforcement (Qi Shi, Ren Junli, Cao Xian, et al. Research on deacidification enhancement of aged paper by in-situ formation of calcium carbonate and nanocellulose [J]. China Papermaking, 2022, 41(05): 52-58.) and polymer reinforcement (CN118531660A), such as nanocellulose reinforcement (CN117779512A), bacterial cellulose reinforcement (CN113802411A), calcium carbonate in-situ synthesis reinforcement and polyvinyl alcohol reinforcement (CN118407277). Among them, natural reinforcement agents are mainly cellulose-based materials, but these materials are prone to acid hydrolysis under acidic conditions. In recent years, researchers have begun to explore the use of aminosilane coupling agents to simultaneously deacidify and reinforce paper (D. Zeng, H. Fan, S.Huang, F. Li, Y. Liao, G. Ge, J. Liu, Study on aging resistance of AAASgrafted in situ on paper documents, Nordic Pulp & Paper Research Journal 38(1) (2023) 99-109.), but the reinforcement effect of this method is usually not as good as that of traditional cellulose-based materials.
[0005] Therefore, aminosilanized modified nanocellulose can be used not only as a deacidifying agent for paper, but also as a reinforcing agent for paper. It can also control the aging process of acidic paper samples, improve the bonding force between fibers, and enhance the mechanical properties of paper, thereby achieving effective protection and restoration of acidic paper samples such as ancient book paper and paper cultural relics.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing aminosilanized nanocellulose for deacidification and reinforcement of paper. Different types of aminosilanized modified nanocellulose are prepared as deacidification agents and reinforcement agents for acidic paper samples by using different aminosilane coupling agents. The method has a simple process and can be prepared in large quantities. Another technical problem to be solved by the present invention is to provide an aminosilanized nanocellulose for deacidification and reinforcement of paper. The effect of the loading amount of modified nanocellulose on the deacidification and reinforcement of acidic paper samples is studied through accelerated aging tests, so as to achieve the purpose of expanding its application scenarios.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing aminosilanized nanocellulose for deacidification and reinforcement of paper comprises modifying pulp fibers with an aminosilane coupling agent and then preparing the aminosilanized nanocellulose through mechanical treatment.
[0010] The method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper comprises the following steps:
[0011] (1) beating the pulp fibers with a pulping machine to obtain pulp fibers that are divided into fibers;
[0012] (2) hydrolyzing the aminosilane coupling agent in a reaction solution, and then mixing the resultant with the pulp fiber obtained in step (1) to obtain aminosilane-modified fiber;
[0013] (3) performing a curing treatment and a solvent replacement treatment on the aminosilane modified cellulose prepared in step (2);
[0014] (4) The modified fibers obtained in step (3) are subjected to mechanical homogenization treatment to obtain aminosilane-modified nanocellulose.
[0015] The type of the aminosilane coupling agent in the step (2) is one of 3-aminopropyltrimethoxysilane and 3-aminopropyl(diethoxy)methylsilane.
[0016] In the step (2), the molar ratio of the aminosilane coupling agent to the pulp fiber is 1-4:1.
[0017] In the step (2), the liquid phase system is one of water, water / ethanol and water / acetone systems, and the reaction time is 2 to 8 hours.
[0018] In the step (3), the curing temperature is 80° C. and the curing time is 8 h. The unreacted aminosilane coupling agent is removed by centrifugation at 8000 rpm.
[0019] The mechanical homogenization treatment pressure in step (4) is 600 bar, and the treatment times are 5 times.
[0020] The aminosilanized nanocellulose prepared by any of the above methods is loaded on the surface of paper to perform deacidification and reinforcement treatment on the paper sample.
[0021] The loading amount of the aminosilanized nanocellulose is 0.25-1.00 g / m 2 .
[0022] The paper is an acidic paper sample with a pH value of ≤5.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] (1) The present invention directly modifies pulp fibers, has a wide range of raw material sources, low production costs, and has high economic advantages.
[0025] (2) The present invention performs a beating process on ordinary pulp to make the pulp fibers fibrillate and expose more hydroxyl groups, thereby increasing their reaction sites.
[0026] (3) The present invention uses ordinary pulp fibers as raw materials, first modifies the pulp fibers and then obtains modified nanocellulose through high-pressure homogenization. The process is simple and can be prepared in large quantities.
[0027] (4) The aminosilanized nanocellulose prepared by the present invention has a good deacidification and strengthening effect on acidified paper samples, and the alkali reserve can reach 0.34 mol / kg. After four days of accelerated aging treatment, compared with the original acidic paper sample, the tensile index of the paper sample loaded with aminosilanized nanocellulose is increased by 164%, and the pH value is stabilized at 6.25.
[0028] (5) The aminosilanized nanocellulose prepared in the present invention can be used to deacidify and strengthen acidified paper samples, thereby effectively protecting precious documents, extending the service life and value of paper, and expanding the application field of nanocellulose materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 Alkali reserve analysis diagram of aminosilanized pulp fibers prepared under different reaction conditions;
[0030] Among them, (a) is an analysis diagram of the alkali reserves of aminosilanized pulp fibers prepared by different reaction liquid phases, the reaction conditions are n (silane coupling agent): n (fiber) = 1~3:1, and the reaction time is 6 h; (b) is an analysis of the alkali reserves of aminosilanized pulp fibers with different silane coupling agent dosages, the reaction conditions are acetone phase, n (silane coupling agent): n (fiber) = 1~4:1, and the reaction time is 6 h; (c) is an analysis diagram of the effects of different types of silane coupling agents on the alkali reserves of aminosilanized pulp fibers, the reaction conditions are acetone phase, and the reaction time is 6 h; (d) is an analysis diagram of the effects of different reaction times on the alkali reserves of aminosilanized pulp fibers, the reaction conditions are acetone phase, and 3-aminopropyl (diethoxy) methyl silane is used.
[0031] Figure 2 Surface morphology of acidified paper samples with different loading amounts;
[0032] Figures (ae) and (h) are the aminosilanized nanocellulose loadings of 0, 0.25, 0.50, 0.75, and 1.00 g / m 2Electron microscopy of the surface of the acidic paper sample, magnification is 1000, scale bar is 50 μm; Figure (f) is the actual picture of the loaded and unloaded paper samples after aging for 3 days. The upper picture is the loading amount of 1.00 g / m 2 The picture below is the acidic paper sample without aminosilanized nanocellulose loading.
[0033] Figure 3 The figure shows the mechanical properties analysis of the acidified paper sample before and after loading. DETAILED DESCRIPTION
[0034] The present invention is further illustrated below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0035] Example 1
[0036] The preparation method of 3-aminopropyltrimethoxysilane modified pulp fiber comprises the following specific steps:
[0037] (1) The pulp is beaten using a PFI mill at a speed of 15,000 rpm and a beating degree greater than 50°SR to obtain fibrillated pulp fibers;
[0038] (2) preparing three liquid phase systems, namely 50 g pure water phase, 50 g ethanol phase (ethanol: water = 9:1), and 50 g acetone phase (acetone: water = 9:1), adding 2.689, 5.379, 8.068 and 10.757 g of 3-aminopropyltrimethoxysilane to the liquid phase, and hydrolyzing at a speed of 400 rpm for 2 h. After the silane coupling agent is hydrolyzed, 2.432 g of pulp fiber with high beating degree in step (1) is added to the container, and reacted at a temperature of 30 ° C for 6 h. The molar ratio of 3-aminopropyltrimethoxysilane to fiber is 1:1, 2:1, 3:1 and 4:1, respectively;
[0039] (3) subjecting the aminosilanized pulp prepared in step (2) to a curing treatment at 80°C for 8 h and a centrifugation operation at 8000 rpm for 10 min three times to obtain an aminosilanized pulp;
[0040] (4) The aminosilane-modified fibers obtained in step (3) were subjected to high-pressure homogenization treatment at a pressure of 600 bar for five cycles to prepare aminosilane-modified nanocellulose.
[0041] like Figure 1(a) is an analysis chart of the alkali reserve of aminosilanized pulp fibers prepared by different reaction liquid phases. It can be found from the figure that under the same reaction time and silane coupling agent dosage, the alkali reserve of aminosilanized pulp fibers prepared by acetone phase is significantly higher than that of the other two liquid phases, increasing from the original alkali reserve of pulp 0.05 mol / kg to 0.18 mol / kg, and the alkali reserve of the modified fiber increases with the increase of silane coupling agent dosage. Figure 1 (b) Analysis of the alkali reserve of aminosilanized pulp fiber in acetone phase with different amounts of silane coupling agent. From the figure, it can be found that under the same reaction liquid phase and reaction time, the greater the amount of aminosilane coupling agent used, the higher the alkali reserve of the modified pulp fiber, which can reach up to 0.25 mol / kg.
[0042] Example 2
[0043] The preparation method of 3-aminopropyl (diethoxy) methyl silane modified pulp fiber comprises the following specific steps:
[0044] (1) The pulp is beaten using a PFI mill at a speed of 15,000 rpm and a beating degree greater than 50°SR to obtain filamentous pulp fibers;
[0045] (2) 2.87, 5.74, 8.611 and 11.841 g of 3-aminopropyl(diethoxy)methylsilane were added to 50 g of acetone solution (acetone: water = 9:1), and the mixture was hydrolyzed at 400 rpm for 2 h. After the silane coupling agent was hydrolyzed, 2.432 g of pulp fiber with high beating degree in step (1) was added to the container, and the mixture was reacted at 30 °C for 6 h. The molar ratio of 3-aminopropyl(diethoxy)methylsilane to fiber was set to 1:1, 2:1, 3:1 and 4:1, respectively.
[0046] (3) subjecting the aminosilanized pulp prepared in step (2) to a curing treatment at 80°C for 8 h and a centrifugation operation at 8000 rpm for 10 min three times to obtain an aminosilanized pulp;
[0047] (4) The aminosilane-modified fibers obtained in step (3) were subjected to high-pressure homogenization treatment at a pressure of 600 bar for five cycles to prepare aminosilane-modified nanocellulose.
[0048] like Figure 1(c) is an analysis chart of the effects of different types of silane coupling agents on the alkali reserve of aminosilanized pulp fibers in the presence of acetone. From the figure, it can be seen that under the same reaction liquid phase and reaction time conditions, the greater the amount of 3-aminopropyl(diethoxy)methylsilane used, the higher the alkali reserve of the modified pulp fibers, up to 0.34 mol / kg. It can also be found that compared with 3-aminopropyltrimethoxysilane, the alkali reserve of pulp fibers modified with 3-aminopropyl(diethoxy)methylsilane is higher.
[0049] Example 3
[0050] Experimental study on preparation conditions of aminosilanized pulp fibers
[0051] The effects of different reaction liquid phases, different aminosilane coupling agent dosages, and different types of aminosilane coupling agents on the alkali reserves of pulp fiber were analyzed. Figure 1 As shown in (ac), in the liquid phase system of acetone: water = 9:1, the alkali reserve of aminosilanized pulp fiber obtained by 3-aminopropyl (diethoxy) methyl silane with 4 times the amount of cellulose substance in the experiment was the highest. The effect of reaction time on the alkali reserve of aminosilanized pulp fiber was also studied, such as Figure 1 (d) The alkali reserves of the modified fibers with reaction times of 2, 4, 6, and 8 h were analyzed. It was found that the alkali reserves of the modified fibers increased with the increase of reaction time, from 0.1 mol / kg to 0.34 mol / kg.
[0052] Example 4
[0053] Determination of aminosilanized nanocellulose loaded on acidified paper samples
[0054] The aminosilanized nanocellulose prepared in Example 1 was added at 0.25, 0.50, 0.75 and 1.00 g / m 2 The loading amount was loaded on the surface of the acidic paper sample by vacuum filtration. The electron microscope images before and after loading are as follows Figure 2 As shown in (ae), the higher the loading, the less pores on the paper surface. When the coating amount is 1.00 g / m 2 When the paper surface pores are completely covered.
[0055] Example 5
[0056] Chromatic difference of acidic paper sample loaded with aminosilanized nanocellulose before and after aging
[0057] like Figure 2 (f) shows the loading of 1.00 g / m after three days of dry heat aging. 2The actual pictures of the acidic paper sample with and without loading show that the color of the acidic paper sample loaded with aminosilanized nanocellulose does not change much with the increase of aging time, and the △E difference is between 0.02-0.06, while the color of the acidic paper sample without loading aminosilanized nanocellulose gradually turns yellow, and its △E difference increases from 0.06 to 1.20.
[0058] Example 6
[0059] Differences in mechanical properties between acidic paper samples loaded with aminosilanized nanocellulose and unloaded acidic paper samples
[0060] like Figure 3 As shown in the figure, the tensile index of the paper sample after four days of dry heat aging, the preparation conditions of aminosilanized nanocellulose are 3-aminopropyl (diethoxy) methyl silane, molar ratio 4:1, liquid phase is acetone phase (acetone: water = 9:1), reaction time is 6 h. The loading amount on the surface of the acidic paper sample is 0.75 g / m 2 Comparison of the mechanical properties of the two paper samples showed that the paper sample loaded with aminosilanized nanocellulose had a higher tensile index of 30.12 N·m / g, which was 53% higher than the tensile index of 19.65 N·m / g of the unloaded paper sample.
[0061] By testing the mechanical properties of paper samples aged for four days, it was found that the tensile index of paper samples loaded with aminosilanized nanocellulose did not change significantly, decreasing from 30.12 N·m / g to 26.88 N·m / g, a decrease of 11%. The tensile index of unloaded paper samples changed significantly, decreasing from 19.65 N·m / g to 10.15 N·m / g, a decrease of 48%.
[0062] By testing the mechanical properties of paper samples on the fourth day of aging, it was found that the tensile index of paper samples loaded with aminosilanized nanocellulose was significantly different from that of unloaded paper samples, which were 26.88 N·m / g and 10.15 N·m / g, respectively. Therefore, aminosilanized nanocellulose can improve the mechanical properties of aged paper samples.
[0063] Example 7
[0064] Difference in pH value between acidic paper sample loaded with aminosilanized nanocellulose and unloaded paper
[0065] Acid paper sample at a load of 0.75 g / m 2 The pH value of the paper sample before aminosilanized nanocellulose was 4.75, and the pH value after loading was 6.25. After four days of dry heat aging, the pH value of the paper sample without aminosilanized nanocellulose loading was 4.22, and the pH value of the paper sample with 0.75 g / m 2The pH value of aminosilanized nanocellulose paper samples remained at 6.22, so aminosilanized nanocellulose can effectively increase the pH value of acidic paper samples and reduce their acidic hydrolysis reaction rate.
[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper, characterized in that: Aminosilane coupling agent was used to modify pulp fiber, and then aminosilane nanocellulose was prepared through mechanical treatment.
2. The method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper according to claim 1, characterized in that: The following steps are involved: (1) beating the pulp fibers with a pulping machine to obtain pulp fibers that are divided into fibers; (2) hydrolyzing the aminosilane coupling agent in a reaction solution, and then mixing the resultant with the pulp fiber obtained in step (1) to obtain aminosilane-modified fiber; (3) performing a curing treatment and a solvent replacement treatment on the aminosilane modified cellulose prepared in step (2); (4) The modified fibers obtained in step (3) are subjected to mechanical homogenization treatment to obtain aminosilane-modified nanocellulose.
3. The method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper according to claim 2, characterized in that: The type of aminosilane coupling agent in step (2) is one of 3-aminopropyltrimethoxysilane and 3-aminopropyl(diethoxy)methylsilane.
4. The method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper according to claim 2, characterized in that: In the step (2), the molar ratio of the aminosilane coupling agent to the pulp fiber is 1-4:
1.
5. The method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper according to claim 2, characterized in that: In the step (2), the liquid phase system is one of water, water / ethanol and water / acetone systems, and the reaction time is 2 to 8 hours.
6. The method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper according to claim 2, characterized in that: In the step (3), the curing temperature is 80° C. and the curing time is 8 h. The unreacted aminosilane coupling agent is removed by centrifugation at 8000 rpm.
7. The method for preparing aminosilanized nanocellulose for deacidification and strengthening of paper according to claim 2, characterized in that: In the step (4), the mechanical homogenization treatment pressure is 600 bar and the treatment times are 5 times.
8. Use of the aminosilanized nanocellulose prepared according to any one of claims 1 to 7 loaded on the surface of paper to deacidify and strengthen the paper sample.
9. The use of the aminosilanized nanocellulose prepared according to claim 8, characterized in that: The loading amount of the aminosilanized nanocellulose is 0.25-1.00 g / m 2 .
10. The use of the aminosilanized nanocellulose prepared according to claim 8, characterized in that: The paper is an acidic paper sample with a pH value of ≤5.
Citation Information
Patent Citations
Protection method suitable for paper homogenization deacidification
CN113186754A
Preparation method of multifunctional paper repair liquid of bacterial cellulose-based alkaline nanoparticles and application of multifunctional paper repair liquid in repair of aged paper
CN113802411A
Preparation method and application of composite deacidification material enabling paper to have high alkali reserves and hydrophobicity after deacidification treatment
CN117107548A
Method for enhancing interlayer binding force of case board by using nano-crystalline cellulose
CN117779512A
Intelligent optimization and control method for deacidification process flow of paper archives
CN118531660A